Sao Tome and Principe : Staff Report for the 2001 Article IV Consultation and Staff-Monitored Program. (IMF Staff Country Reports; Country Report ;, 2002)
This paper assesses the 2001 Article IV Consultation and Staff-Monitored Program (SMP) for Sao Tome and Principe. Fiscal slippages, delays in structural reforms, and governance problems during the fourth quarter of 2000 and the first three quarters of 2001 led to the program going off track. The key quantitative performance criterion on the primary budget balance and the quantitative benchmark on government spending were not observed at either end-December 2000 or end-June 2001. The SMP is intended to correct the slippages incurred in 2001 and reestablish a track record of policy implementation.